Reconstruction of the glacial history after the Last Glacial Maximum in the Italian Central Alps using Schmidt's hammer R-values and crystallinity ratio indices of soils. (30th August 2020) - Longhi, A.; Guglielmin, M.
Abstract: Despite the ongoing development of cosmogenic techniques to reconstruct deglaciation and glacial advances, these techniques are not always feasible for logistical and economic reasons. In this study, we used Schmidt Hammer R-values (SH) and Crystallinity Ratio (CRF) indices of soils, together with a limited number of absolute 14 C dates, to outline the glacial evolution of the Gavia Valley. The study area is a sector of the Italian Central Alps with a glacial history that is poorly understood. Methodologically, we found that SH can be successfully applied to Late Pleistocene surfaces younger than 15ka in this Alpine region. The SH method generally underestimates the ages with respect to the CRF indices and the 14 C dates. A total of 7 different glacial phases were found in the study area: 14.7ka (I phase), 13.7ka (II phase), 12.2–11.8ka (III phase), 10.2–9.7ka (IV phase), 7.5ka (V phase), 5.5ka (VI phase), 1.9ka (VII phase). These phases are generally consistent with the literature; however, the Little Ice Age was surely less extended respect the other Holocene advances (V and VI phase). This suggests that relatively short climatic variations during the Holocene were locally important.